2017
DOI: 10.1364/oe.25.010449
|View full text |Cite
|
Sign up to set email alerts
|

Inner structure of ZnO microspheres fabricated via laser ablation in superfluid helium

Abstract: ZnO microspheres fabricated via laser ablation in superfluid helium were found to have bubble-like voids. Even a microsphere demonstrating clear whispering gallery mode resonances in the luminescence had voids. Our analysis confirmed that the voids are located away from the surface and have negligible or little effect on the whispering gallery mode resonances since the electromagnetic energy localizes near the surface of these microspheres. The existence of the voids indicates that helium gas or any evaporated… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Laser ablation, or sputtering, is a unique in-situ preparation method to produce atoms, ions, and nano/microparticles in various environments; it is also applicable to superfluid 4 He. Laser ablation in superfluid 4 He has been used for precision spectroscopy[1-3], tracer injection [20], nano/micro structure formation [5,6], and optical manipulation/trapping [21,22]. In this study, we observed the silicon nanoparticledecorated, suspended quantised vortices, and identified the vortex reconnection events [13], the dynamics of which were found to be consistent with the results of dimensional analysis the simple vortex filament model (VFM) calculations.…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Laser ablation, or sputtering, is a unique in-situ preparation method to produce atoms, ions, and nano/microparticles in various environments; it is also applicable to superfluid 4 He. Laser ablation in superfluid 4 He has been used for precision spectroscopy[1-3], tracer injection [20], nano/micro structure formation [5,6], and optical manipulation/trapping [21,22]. In this study, we observed the silicon nanoparticledecorated, suspended quantised vortices, and identified the vortex reconnection events [13], the dynamics of which were found to be consistent with the results of dimensional analysis the simple vortex filament model (VFM) calculations.…”
Section: Introductionsupporting
confidence: 64%
“…
Impurity injection into superfluid helium is a simple yet unique method with diverse applications, including high-precision spectroscopy[1-3], quantum computing[4], nano/micro material synthesis [5,6], and flow visualisation [7]. Quantised vortices are believed to play a major role in the interaction between superfluid helium and light impurities [2,[8][9][10][11].
…”
mentioning
confidence: 99%
“…Figure 1E shows the typical SEM image of the synthesized zinc oxide particles. The zinc oxide particles are highly spherical (28), which is suitable for optical trapping. Many synthesized zinc oxide particles have dimensionalities in the stability-size regime, although its difficult to control the synthesized particle size distribution.…”
Section: Particle Loadingmentioning
confidence: 99%
“…Determining the trapped particle size is very necessary because the size governs the interaction between the particle and the surrounding quantum fluid. In our study, zinc oxide particles of sizes ranging from nanometres to micrometres (28) were fabricated through the laser ablation process. We demonstrate the size determination of the actual trapped particle using the Mie scattering theory (29).…”
Section: Optical Trapping In Superfluid Heliummentioning
confidence: 99%
“…Minowa and associates find that ZnO microspheres produced by laser ablation in superfluid helium contain bubble-like voids, even though they act as whispering gallery mode laser cavities [7]. The authors suggest that helium gas (or evaporated target material) contained in molten ZnO particles may create voids in the microspheres.…”
Section: Materials Processing By Structured Lightmentioning
confidence: 99%